PEGylated gas vesicles: a promising novel ultrasound contrast agent for diagnosis and guiding radiofrequency ablation of liver tumor - Kezhi Yu; Yongquan Huang; Yuanyuan Wang; Qunyan Wu; Zihang Wang; Fei Li; Jianri Chen; Maierhaba Yibulayin; Shushan Zhang; Zhongzhen Su; Fei Yan (Journal of Nanobiotechnology)
Abstract Ultrasound contrast agents (UCAs) play an important role in diagnosis and the imaging-guided treatment of liver tumor in clinical settings. However, most commercially available UCAs are micro-sized and fabricated through a chemical synthesis route. Here, we developed a new class of biosynthesized nanoscale contrast agent (PEG-GVs) and comprehensively compared its physicochemical characteristics and imaging performance with commercial Sonovue and Sonazoid. Our results revealed PEG-GVs may produce more stable and durable contrast signals, contributing to their penetration beyond blood vessels and long-time retention in liver. Interestingly, we found that PEG-GVs did not exhibit a continuously enhanced accumulation in the liver tumor due to the EPR effect, but displayed a rapid regression. The long-time retention of PEG-GVs in normal liver tissue and rapid regression from liver tumor lead to distinct display of liver tumor boundaries, enabling the early diagnosis of small liver metastases and presenting advantages in guiding radiofrequency ablation of liver tumor. Moreover, we have also verified that PEG-GVs exhibit excellent imaging performance and biosafety in macaques. Our study provides new insights into the roles of PEG-GVs in liver tumor diagnosis and ablation guidance.